Effect of Pellet Die Thickness and Conditioning Temperature During the Pelleting Process on Phytase Stability - C. N. Truelock; N. E. Ward; J. W. Wilson; C. R. Stark; C. B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2019)
This experiment was designed to evaluate the effects of pellet mill die thickness and conditioning temperature on the stability of microbial phytase. Treatments were arranged as a 2 × 3 factorial of die thickness (L:D 5.6 and 8.0) and conditioning temperature (165, 175, and 185°F). Phytase was added to a corn-soybean meal-based diet and mash samples were collected for phytase analysis. The diet was pelleted via steam conditioning (10 × 55 in Wenger twin staff pre-conditioner, Model 150) and using a pellet mill (CPM Model 1012-2) with a 5/32 × 7/8 in (L:D 5.6) or 5/32 × 1 1/4 in (L:D 8.0) pellet die. Conditioner retention time was set at 30 sec and production rate was set at 33 lb/min, approximately 100% of the rated throughput for the pellet mill. All treatments were replicated on 3 separate days. Pellet and conditioned mash samples were collected and immediately placed in an experimental counter-flow cooler for 15 min. For each treatment, pellet and conditioned mash samples were composited such that 2 samples of each were analyzed for phytase activity and pellet durability index (PDI). Conditioning temperature, hot pellet temperature (HPT), and production rate were recorded throughout each processing run. Data were analyzed using the GLIMMIX procedure in SAS (v. 9.4), with pelleting run as the experimental unit and day as the blocking factor. There was no evidence (P>0.14) for a die thickness × conditioning temperature inter- action for any of the pelleting or phytase responses analyzed in this study. Hot pellet temperature was increased when diets were pelleted with a thicker die (P<0.01), and by increasing conditioning temperature from 165 to 185°F (linear,P<0.01). Pellet durability index was greater (P<0.01) for diets pelleted using the thicker die with an 8.0 L:D compared to the die with a 5.6 L:D. Additionally, PDI increased (linear,P= 0.03) with increasing conditioning temperature. Increasing conditioning temperature from 165 to 185°F decreased (linear,P<0.01) phytase stability of conditioned mash and cooled pellets, with no difference (P>0.72) in stability due to die thickness. Results of this experiment show that phytase stability in conditioned mash and pellets decreases linearly when conditioning temperature rises above 165°F and HPT rises above 177°F. Although the thicker pellet die increased HPT by an average of 1.9°F and increased PDI by an average of 7.8%, there was no evidence that the additional frictional heat associated with increasing the die L:D from a 5.6 to an 8.0 resulted in lower phytase stability. Finally, increasing conditioning temperature linearly increased HPT and PDI.
Keywords: conditioning temperature; die thickness; pelleting; phytase stability